Digital Payments in Indonesia: Understanding the Effect of Application Security on User Trust - Rabbani, Maheswara; Wijaya, Juan Daniel; Kusuma, Rendy Sanjaya; Purba, Wilhelmus Billion Pius; Tajib, Robert Marchelino (The Indonesian Journal of Computer Science, 2023)
Technological developments present digital payment innovations for fast and practical transaction processes. Many digital wallets (e-wallet) services have emerged recently, becoming a trend in Indonesia. However, digital payments carry the risk of hacking user accounts, fraud (scams), phishing, and other criminal acts that aim to steal users' personal information. Financial is a sensitive issue; security is essential to digital payments. The research aims to analyze the effect of application security on user trust when making online transactions using digital payment applications. The study used a descriptive statistical method by distributing questionnaires to 50 Indonesians who have made electronic payments at least once for transactions. The study results show that application security significantly affects user trust in digital payments. Research results from various references show that application security influences impulse buying behavior and intentions to use e-wallet platforms.